Marketing strategies based on ICT for the enterprise "Ricaurte" Moniquirá - Boyacá (Revista cientifica In Vestigium Ire, 2019)
This article is the result of a scientific research process where marketing strategies are proposed in arder to have greater communication between the company, customers and suppliers and show the benefits of entering the trade using lnformation and Communications Technology - ICT, in the snack producing company "Ricaurte" far planning, execution, customer service and marketing processes. lnitially, a bibliographic review is carried out later, the most appropriate business diagnostic methodology is chosen, DT-SMEs being the ones; subsequently, howto make use of their strengths and control disadvantages, using technological tools that lead to the display of their products through Internet, identifying their sales potential thus satisfying the needs of the client.
Keywords: electronic commerce; small business; e-commerce